A new approach for determination of free carriers lifetime and density of localised states in disordered semiconductors. Issue 2 (17th January 2019) - Belgacem, H.; Reynolds, S.
ABSTRACT: A new method for measuring the free carriers lifetime ( ) and the density of localised states (DOS) in amorphous semiconductors is described. The method is based on the analysis of transient photoconductivity (TPC) data using Laplace transform technique. This technique involves Laplace transform of TPC data, it is a simple analysis of the solution of the basic linearised multiple trapping equations for free and trapped electrons. It is demonstrated by application to simulated and experimental TPC data measured on a typical disordered semiconductor, the hydrogenated amorphous silicon (a-Si:H). An introduced in the computing of the TPC using an arbitrarily proposed DOS model is recovered with high accuracy. For the experimental case, the determination of the exact DOS and the estimated from the experimental TPC data allow to reconstruct accurately this last. The performance and limitations of the technique are studied by means of computer simulations. Limitations are essentially the low temperatures of measurement of TPC when the recombination phenomenon is not observed at short times.